Conservation Tools, Protocols and Treatments on Painted Surfaces, Metal Leaves and Finishes in Cultural Heritage - Marco, Nervo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Conservation of painted surfaces, metal leaves, and finishes requires a deep knowledge of both the materials themselves and the supports and the interaction phenomena occurring among them. Superficial treatments, operations, and materials adopted during the conservation intervention can modify the complex system of existing interactions. Therefore, it is fundamental to predict possible induced changes of the chemical-physical properties of the systems. This Special Issue aims at contributing to the definition of the state-of-the-art in the approach to conservation problems of painted surfaces, metal leaves, and finishes. In particular, the topic of interest includes but is not limited to: Methodological approaches for the conservation treatments of the painted surfaces, metal leaves, and finishes; Analytical tools and protocols for the validation of the treatment efficacy and recognizability; Analytical tools for the characterization of surface materials and their decay processes; New materials and treatments.